Investigating the functional organisation of human visual cortex using ultra-high resolution fMRI - Finnegan, S (2016)
Current thinking suggests that specialised modules process visual information in a hierarchical manner, using local circuitry in order to maximise efficiency both in terms of wiring costs and stimulus coverage (Reichl et al. (2012)). The resulting organisation has been shown to contain structure in the form of stripes, columns and pinwheels, which in animal models have been linked to functional segregation and specificity. In human cortex, post-mortem investigations have assisted in the visualisation of two such key features: ocular dominance columns (ODC) within V1, and a stripe system within V2 (Adams et al. (2007); Hockfield et al. (1990)). However, functional observations in humans have until recently been beyond the investigatory scope of in-vivo methodology, and as such, a role of these networks has yet to be conclusively determined. In the small number of instances of in-vivo investigations of human ODC and V2 stripes (Cheng et al. (2001); Yacoub et al. (2001); Nasr et al. (2016)), data have been acquired for a small number of carefully selected participants over long scan durations. I aimed to overcome these limitations and explore the functional similarities further, employing a novel, ultra-high resolution fMRI sequence to do so. I measured the cortical response to monocular stimulation and recorded a robust response within V1. However, the regular and repeating functional patterns of ODCs were not observed. Using multivariate techniques I concluded, based on robust classification, that reliable monocular signals were present but that they were subtle and difficult to differentiate from noise. I then investigated the segregation of colour, form and motion within V2, where I found evidence for spatially segregated signals in response to colour and motion, but not to form. I hypothesised that the form stimulus was sub-optimal in driving the neural population of the associated stripes. Based on a limited number of samples, activity in response to colour and motion stimulation conformed on average to the neuroanatomical profile of the V2 stripe system. I suggest that my results offer encouragement for in-vivo investigations of small-scale functional organisation in visual cortex.